1989
DOI: 10.1084/jem.169.3.823
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin and tumor necrosis factor challenges in dogs simulate the cardiovascular profile of human septic shock.

Abstract: Endotoxin, an LPS found in the outer membrane of Gram-negative bacteria, has been considered by many to be the principal toxin involved in the pathogenesis of Gram-negative septic shock (1). However, it is now clear that endotoxin may cause most (ifnot all) of its biological effects via the release of host factors (2-5) . Several studies have suggested that TNF, a cytokine produced by macrophages during septic shock, is one ofthe endogenous mediators that causes cardiovascular injury and death (2-5).Previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
183
2
5

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(202 citation statements)
references
References 24 publications
9
183
2
5
Order By: Relevance
“…As mentioned earlier, endotoxin might have caused a transient LV systolic dysfunction (8,9), but both endotoxin itself and endotoxin-producing bacteria were not detected from the sera of this patient. As a consequence, it was suggested that this patient's heart failure might have been due to functional depression of myocardial contractility resulting from a direct effect of the cytokines towards the cardiomyocytes, a pathophysiologic state compatible with the so-called "septic myocardial depression".…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As mentioned earlier, endotoxin might have caused a transient LV systolic dysfunction (8,9), but both endotoxin itself and endotoxin-producing bacteria were not detected from the sera of this patient. As a consequence, it was suggested that this patient's heart failure might have been due to functional depression of myocardial contractility resulting from a direct effect of the cytokines towards the cardiomyocytes, a pathophysiologic state compatible with the so-called "septic myocardial depression".…”
Section: Discussionmentioning
confidence: 98%
“…This condition has been termed "septic myocardial depression (6)" or "acute septic cardiomyopathy (7)". Endotoxin (8,9), TNF-a (9) and ILip (10) have been reported to induce the same hemodynamic changes as seen in the clinical settings; hypotension and decrease in cardiac output, systemic vascular resistance and LVEF (8,9). Experimental studies (6, 7, 10, ll) have shown that proinflammatory cytokines such as TNF-a (6, 7, 10, 1 1) and IL-ip (6, 7, 10) induce a negative inotropic effect through nitric oxide (NO)-dependent (6, 10) or NO-independent (6, 7, 10, ll) mechanisms; TNF-a is reported to exert its myocardial depressant effects by activation of myocardial constitutive NOsynthase (CNOS)and gene expression of inducible NOS (iNOS) leading to increased NO production.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive TNF production may turn TNF activities from beneficial to extremely injurious. In fact, acute release of large amounts of TNF in the circulation is followed by the characteristic manifestations of septic shock, i.e., decrease in capillary resistance, capillary leakage, falling in cardiac output, diffuse coagulation with necrosis of vital organs, and cardiopulmonary collapse (47)(48)(49). PMN are crucial targets of TNF activity, and if exposed to high TNF doses they may become key effectors of its toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…1; [84]). Dieselbe Arbeitsgruppe konnte 4 Jahre später zeigen, dass ihre Ergebnisse auf dem Vorhandensein von Tumor-Nekrose-Faktor-α (TNF-α) beruhten [76]. In folgenden Untersuchungen wurde belegt, dass hierbei auch Interleukin-1β (IL-1β) eine Rolle spielt [53], und mehrere jüngere Studien postulieren eine Schlüsselrolle für diverse proinflammatorische Zytokine (.…”
Section: Zirkulierende Faktoren Zytokine Und Stickstoffmonoxidunclassified